2017
DOI: 10.3727/105221617x15016197658871
|View full text |Cite
|
Sign up to set email alerts
|

Cell Death and Prognosis of Mortality in Alcoholic Hepatitis Patients Using Plasma Keratin-18

Abstract: Alcoholic liver disease encompasses the progressive stages of liver dysfunction that culminates in alcoholic cirrhosis (AC) and in severe cases alcoholic hepatitis (AH). Currently, prognostic scores have limited specificity and sensitivity. Plasma keratin-18 (K18) levels are elevated during liver disease and may be biomarkers of outcome. The objective of this study was to determine if total K18 (M65) or caspase-cleaved K18 (M30) levels were different between AC and AH patients. M65 and M30 levels were measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 44 publications
(71 reference statements)
2
38
0
Order By: Relevance
“…Moreover, there was a reduction in the cK18-to-K18 ratio indicating that the presence of necrotic cell death is associated with non-survival (3). These observations largely mirror previous data found in alcoholic hepatitis patients by our own group (5). Further studies are necessary in this area in large, multi-institutional cohorts to validate the potential for cK18-to-K18 ratio or the individual values alone to predict mortality (7).…”
supporting
confidence: 92%
See 3 more Smart Citations
“…Moreover, there was a reduction in the cK18-to-K18 ratio indicating that the presence of necrotic cell death is associated with non-survival (3). These observations largely mirror previous data found in alcoholic hepatitis patients by our own group (5). Further studies are necessary in this area in large, multi-institutional cohorts to validate the potential for cK18-to-K18 ratio or the individual values alone to predict mortality (7).…”
supporting
confidence: 92%
“…Further studies are necessary in this area in large, multi-institutional cohorts to validate the potential for cK18-to-K18 ratio or the individual values alone to predict mortality (7). Multiple studies have now confirmed increases in K18 and cK18 in AH patients (5,6). The current study largely confirms these data but notes that due to near ubiquitous increases in K18 and cK18 in clinically relevant liver diseases, these parameters alone may not be sufficient for establishing ACLF/alcoholic hepatitis (3).…”
mentioning
confidence: 89%
See 2 more Smart Citations
“…Other biomarkers such as miR-122 [244247], full-length cytokeratin-18 [247250], high mobility group box 1 (HMGB1) protein [247249, 251], and argininosuccinate synthetase (ASS) [252] are generally considered indicators of mainly necrotic cell death [253]. On the other hand, increased plasma levels of the caspase-cleaved form of cytokeratin-18 [247, 248, 250, 254, 255] and activated caspases detected as enzyme activity and/or the protein by western blotting [164, 247, 249, 254], are markers of apoptotic cell death. However, due to the sensitivity of the assay, cleaved cytokeratin-18 levels should always be compared to the full-length version in order to assess the relative importance of apoptosis [247, 248, 254].…”
Section: Mitochondrial Biomarkers In Drug-induced Liver Injurymentioning
confidence: 99%